이벤트 알림 서비스의 구조와 성능분석 - 한영태(Youngtae Han); 민덕기(Dugki Min) (韓國컴퓨터情報學會論文誌, 2005)
Event notification service is a event-based messaging middleware service needed for various vertical domains, such as, business applications, distributed system management, and web service integration. In this paper, we investigate the architecture of an event notification service that includes a subject-based event dissemination service and a flexible message communication service. The event dissemination service is in charge of transferring events asynchronously but speedy according to the subjects of events and their environmental knowledge. It also includes content-based message filtering. The message communication service provides a common communication infrastructure supporting variety types of messages and variety of protocols. Depending on application domains and situation, we can re-configurate the communication infrastructure in order to optimize the efficiency and usability. This paper shows the performance analysis of our event notification service with various types of message formats and protocols. 이벤트 알림 서비스는 이벤트 기반의 메시징 서비스 미들웨어로 비즈니스 응용 프로그램, 분산 시스템 관리, 그리고 웹 서비스 통합을 위한 응용 프로그램 영역에서 사용하고 있다. 본 논문에서는 주제 기반의 이벤트 분배 서비스와 다양한 메시지 통신 서비스를 제공하는 이벤트 알림 서비스 아키텍처를 제시한다. 이벤트 분배 서비스는 이벤트들을 비동기적인 방식으로 전송하며 이벤트에 정의된 주제 정보와 시스템의 환경 정보를 활용하여 이벤트 전송이 빠르게 하였다. 또한 이벤트의 내용에 대한 필터링 기능을 포함하고 있다. 메시지 통신 서비스는 다양한 형식의 메시지와 다양한 통신 프로토콜을 지원하기 위한 통신 인프라스트럭처이다. 응용 프로그램의 도메인과 환경에 따라, 통신 인프라스트럭처는 성능과 유용성을 최적화하기 위해 재배치하여 사용할 수 있다. 본 논문에서는 우리가 개발한 이벤트 알림 서비스에 대한 성능 분석한 결과를 다양한 형식의 메시지 형식과 통신 프로토콜을 대상으로 제시한다.